Valoración económica de la cuenca urbana del río Tunjuelo utilizando transferencia de beneficios (2020)
The transfer of benefits is an indirect valuation and declared preferences method that is used as a second best option when there are time, budget or information restrictions that prevent valuation with primary studies. This document makes a valuation proposal for the ecosystem services of the Tunjuelo River through a transfer function. This is defined from a choice experiment for the Ciliwung River in Jakarta by the similarities in the restoration project evaluated, the ecosystem services considered, the socioeconomic characteristics and the quality of its methodology. The benefit function assesses flood mitigation, landscape value of public space and biodiversity due to the presence of vegetation. In turn, a spatial analysis of the valuation is presented through geographic information systems (GIS) for the 31 zonal planning units (UPZ) in order to identify the spatial variability of the ecosystem services and thus identify areas of environmental priority. The exercise found a consumer surplus or willingness...